2013
DOI: 10.1186/1897-4287-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Experience of BRCA1/2 mutation-negative young women from families with hereditary breast and ovarian cancer: a qualitative study

Abstract: BackgroundLittle is known about the experience of young women who become aware of their parent’s BRCA1 or BRCA2 (BRCA) mutation status as adolescents or young adults. There is also currently a gap in the literature pertaining to those who are found to be negative for their familial mutation. We aimed to investigate the experience of these mutation-negative young women from hereditary breast and ovarian cancer (HBOC) families.MethodsUsing a semi-structured questionnaire we interviewed 8 women. All of the women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…Some continued to have residual cancer worry and desired to have additional screening yet did not seek out further treatment or screening beyond what was recommended to the general population for their age. 70 Recently, there has been increased attention to individuals who receive a test result of variants of unknown significance (VUS). A VUS is an unclassifiable variant in the gene being studied for which too little data are currently available with which to make an interpretation as a benign polymorphism (ie, no association with disease risk) or a mutation.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some continued to have residual cancer worry and desired to have additional screening yet did not seek out further treatment or screening beyond what was recommended to the general population for their age. 70 Recently, there has been increased attention to individuals who receive a test result of variants of unknown significance (VUS). A VUS is an unclassifiable variant in the gene being studied for which too little data are currently available with which to make an interpretation as a benign polymorphism (ie, no association with disease risk) or a mutation.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…Those who receive negative results may still experience distress as "survivor's guilt." 70 Inconclusive or indeterminate results can also be stressful with their unclear meaning about future risks.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 Two sets of authors reported that the first communication about the genetic risk was made by parents. 14,16 None of the participants was younger than 12 years of age when informed, about half experienced disclosure before they were 18 years old and half between 18 and 21 years old. Many participants stated that the disclosure was made during an occasional encounter and in a casual moment (ie, while driving) or by telephone.…”
Section: Presymptomatic Genetic Testing In Young Adultsmentioning
confidence: 99%
“…15 Samples included participants within an age range of 12-39 years, thus including, but not limited to, the age range of 14-30 years identified by the authors as the focus of the search. Eligible studies were conducted in Australia, 12,13,15,17 Canada, 14,18,19 United Kingdom, 11 and the United States. 16 …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation